A retrospective multicenter study of oral and maxillofacial lesions in older people - John Lennon Silva CUNHA; Israel Leal CAVALCANTE; Ana Beatriz Rocha RODRIGUES; Niely Enetice de Sousa CATÃO; Vitória Maria Sousa CRUZ; Eveline TURATTI; Roberta Barroso CAVALCANTE; Felipe Paiva FONSECA; Manuel Antonio GORDÓN-NÚÑEZ; Pollianna Muniz ALVES; Cassiano Francisco Weege NONAKA; Bruno Augusto Benevenuto de ANDRADE (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Few studies on the distribution of oral diseases in older people are available in the literature. This study aimed to investigate the prevalence and demographic characteristics of oral and maxillofacial lesions in geriatric patients (age ≥ 60 years). A retrospective descriptive cross-sectional study was performed. Biopsy records were obtained from archives of three Brazilian oral pathology centers over a 20-year period. Data on sex, age, anatomical site, skin color, and histopathological diagnosis were collected and analyzed. Pearson's chi-square test was used to evaluate differences in the frequency of the different oral and maxillofacial lesion groups. A total of 7,476 biopsy records of older patients were analyzed. Most cases were diagnosed in patients aged 60 to 69 years (n = 4,487; 60.0%). Females were more affected (n = 4,403; 58.9%) with a female-to-male ratio of 1:0.7 (p < 0.001). The tongue (n = 1,196; 16.4%), lower lip (n = 1,005; 13.8%), and buccal mucosa (n = 997; 13.7%) were the most common anatomical sites. Reactive and inflammatory lesions (n = 3,840; 51.3%) were the most prevalent non-neoplastic pathologies (p < 0.001), followed by cysts (n = 475; 6.4%). Malignant neoplasms were more frequent (n = 1,353; 18.1%) than benign neoplasms (n = 512; 6.8%). Fibrous/fibroepithelial hyperplasia (n = 2,042; 53.2%) (p < 0.001) and squamous cell carcinoma (n = 1,191; 88.03%) (p < 0.001) were the most common oral lesions in older adults. Biopsy data allow the accurate characterization of the prevalence of oral and maxillofacial lesions, supporting the development of public health policies that can enable the prevention, early diagnosis, and appropriate treatment of these lesions. Also, they bring valuable information that helps dentists and geriatricians diagnose these diseases.